Spiritualitas dan Kebijaksanaan dalam Puisi Rumi Love Poems, Ilustration dan Sadi Bustan dan Gulistan: Cinta Illahi, Moralitas dan Makna Hidup - Mawaddah, Luthfiyya Fariha; Nurholis Nurholis; Azzahra, Bunga Aulia; Supriatin, D Allya Putri (Pusat riset dan Inovasi Nasional, 2025)
Divine love is the ultimate goal of human life and occupies the highest maqam in the spiritual journey. This love begins from self-love that grows because it always remembers the Creator (Allah), then dissolves in dhikr and deep spiritual contemplation, until a person begins to let go of his attachment to the world and prefers closeness to Allah. Love for Allah is a deep mental condition, in which the beloved (human) is willing to open the veil of his ego in order to welcome the presence of the true Lover (Allah). In this context, Jalaluddin Rumi's thinking is particularly relevant, especially when viewed philosophically as to how Divine love becomes possible to grow in a person. It can also be seen as an answer to the disruptive attempts of Western thought that tend to separate spirituality and human existence. Morality is a principle that is closely related to good and bad in human behavior. Human actions are inseparable from moral judgment, whether they are right or wrong, good or bad. Humans as spiritual beings have an awareness of the meaning and purpose of life, different from other beings who, although intelligent, do not have an existential dimension and transcendent consciousness. This awareness is the basis for the emergence of moral responsibility and the search for the true meaning of life.